Pengaruh Variasi Metode Ekstraksi Metabolit Sekunder Bakteri Endofit Daun Rambutan (Nephelium lappaceum L.) terhadap Pertumbuhan Escherichia coli dan Bacillus subtilis - Hasyim Abdurrasyid; Ibnul Mubarok; Dewi Mustikaningtyas; Pramesti Dewi (Life Science, 2024)
Rambutan (Nephelium lappaceum L.) is one of the many tropical plants found in Indonesia. The leaves of the rambutan plant are known to be used as medicine, so they have the potential to be a source of endophytic bacteria that can produce beneficial compound. This study aims to isolate, identify of endophytic bacteria from rambutan leaves, and test their activity as an antibacterial with two different secondary metabolite extraction methods, namely maceration with 70% methanol and without maceration. This study used experimental research with a Completely Ramdomized Design (CRD). Isolation of endophytic bacteria from rambutan leaves produced two isolates (D1 and D2). The results of identification through macroscopic, microscopic, and biochemical test showed that two pure isolates had similarities to genus Bacillus sp. Antibacterial activity testing was carried out using well diffusion method. Based on the results of antibacterial test showed that extraction method with 70% methanol produced an extract that was more effective as an antibacterial with average diameter of clear zone formed for Escherichia coli bacteria were 13.55 mm (Isolate D1) and 12.13 mm (Isolate D2) and that of Bacillus subtilis bacteria were 16.27 mm (Isolate D1) and 19.69 mm (Isolate D2). This finding contributes to the fact that the type of secondary metabolite extraction method of rambutan leaf endophytic bacteria influences the sensivity as an antibacterial.